INNOVATIVE APPROACH IN UNDERSTANDING QURANIC LINGUISTICS MIRACLE USING “METHODOLOGY OF GENERATIVE GRAMMAR AND TRANSFORMATIONAL TO DEVELOP MODEL MODULE AI DIDACTIC “(Mgg&Tf@Llmm-AI-Dc)“ - Abdul Rahman, Asma; Almazroui, Karima Matar; Md Din, Omar; Abdul Rahman, Maryam (Journal of Advanced Research Design, 2025)
This research aims to develop an example model module fo IPTstudents to learn linguistic model module AI Didactic “(Mgg&Tf@Llmm-AI-Dc)“through the holy verses of the Quran. This research employs Richey and Klein's Design and Development Research Approach (DDR (2007). Three phases based on this method were involved in this study. The first phase involved a needs analysis using the interview method with three lecturers to identify the needs of IPT students in learning linguistic model modul AI Didactic through the Quran. In this phase, the researcher used the Discrepancy Model by Mckilli (1987) as a guideline for constructing interview questions. This is followed by constructing an example module of the linguistic model module AI Didactic through the Qur'an in the second phase. In this phase, the researcher uses the Fuzzy Delphi method by looking at the agreement of the experts in building the content of the module. Besides, LEXICOLESM Module Development Model (2004-2024) was chosen as a model for developing the module.This phase has resulted in a draft of an example module for learning linguistic model module AI Didactic through the Qur'an that is suitable for IPT students. The third phase involves evaluating the module's suitability and usability. In this phase, the researcher used the semi-structured interview method as an instrument for data collection involving five lecturers Interview questions were built based on the Discrepancy Evaluation Model by Provus (1966). This study is expected to build an example module that is suitable for learning linguistic model module AI Didactic al-Quran for IPT students.